Treatment of Advanced Parkinson's Disease - Sara Varanese; Zoe Birnbaum; Roger Rossi; Alessandro Di Rocco (Parkinson's Disease)
Patients at late stage Parkinson's disease (PD) develop several motor and nonmotor complications, which dramatically impair their quality of life. These complications include motor fluctuations, dyskinesia, unpredictable or absent response to medications, falls, dysautonomia, dementia, hallucinations, sleep disorders, depression, and psychosis. The therapeutic management should be driven by the attempt to create a balance between benefit and side effects of the pharmacological treatments available. Supportive care, including physical and rehabilitative interventions, speech therapy, occupational therapy, and nursing care, has a key role in the late stage of disease. In this review we discuss the several complications experienced by advance PD patients and their management. The importance of an integrative approach, including both pharmacological and supportive interventions, is emphasized.